Daily field checking list by Walter Rosene, May 5, 1941 - Rosene, Walter M., Sr., 1880-1941et al; Iowa Ornithologists' Unionet al
Daily field checking list of birds observed in Boone County by Walter Rosene, May 5, 1941. Also notes that the American Goldfinches were singing loudly. Plustek--flatbed